2015
DOI: 10.1016/j.buildenv.2015.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Plant cover and floristic composition effect on thermal behaviour of extensive green roofs

Abstract: a b s t r a c tIn the last few years an increasing attention has been paid to efficient energy construction systems in the building sector. Although in this contest extensive green roofs are reported to be very effective and sustainable systems, the fact that the main agents of this systems are living organisms have generated doubts, especially in locations where the development of plants and vegetation can be greatly affected by climate. This study aims to investigate the thermal performances of a 2000 m 2 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 29 publications
0
27
0
2
Order By: Relevance
“…The green roof models (the layers and the plants used) are presented in Figure 5. While working out the thickness and materials for each layer, we took into account the construction solutions for this type of model design in the laboratory scale used by various researchers [25,[94][95][96]. The soil substrate layers composition in the laboratory model were made according to the author's own idea.…”
Section: Discussionmentioning
confidence: 99%
“…The green roof models (the layers and the plants used) are presented in Figure 5. While working out the thickness and materials for each layer, we took into account the construction solutions for this type of model design in the laboratory scale used by various researchers [25,[94][95][96]. The soil substrate layers composition in the laboratory model were made according to the author's own idea.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that among all sections in the building envelope, the roof of a building is a key point for improving the indoor temperature since the surface temperature generally is the highest in that place, and the heat transfer of the roofs is maximum in the summer, [10]. The analysis showed that the role of green roofs on cooling load reduction was at a maximum (about 60%) for the last floor and the second last floor (about 58%), in results in the whole building about 2 to 39% of the total load depends on the number of floors, and less in high-rise buildings [14,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the implementation of Green Architecture and Smart Architecture in Taiwan is unable to identify the effectiveness of energy-saving and carbon emission reduction as well as reduction in environmental pollution. Therefore, the architecture industry in Taiwan is still an industry which emits high CO 2 , and high CO 2 , causes issues such as environmental damage, greenhouse effect, abnormal weather, and climate change etc. (Khan et al, 2016;Heidari and Pearce, 2016).…”
Section: Introductionmentioning
confidence: 99%